The effects on food intake and nutrient digestibility of different conservation methods of whole crop barley harvested at boot stage in lambs - Gürdogan, F; Tatli, P; Çerçi, IH; Azman, MA (Scientific Technical Research Council Turkey, 2002)
This study was conducted to determine the effects on food intake and nutrient digestibility of different methods of conservation of whole crop barley harvested at boot stage and the feasibility of producing whole crop barley as a second crop after cereal harvest. In this study, six male 8-month-old Akkaraman lambs were used. The experiment was carried out with individual boxes of 6X6 Latin square design. This study included six groups. The Pc group was ensiled after wilting 24-48 h under a roof, the Pt group was ensiled after wilting for 24-48 h on the ground, the Y+S group was ensiled while fresh by adding straw treated with HCl (fresh material 80%+straw 20%), the Y group was ensiled fresh on the day of harvesting, the Kt group was dried on the ground and the Kc group was dried under a roof. The pH of silages and dry matter levels were determined to be 4.16, 4.25. 3.65 and 3.92: 31.91, 32.14. 31.30. 20.39, 89.26, 90.07% in the Pc, Pt. Y+S, Y, Kt and K groups, respectively. Dry matter intakes of lambs were determined to be 825.42, 781.46, 803.57, 739.77, 564.95 and 714.57 gin the P, Pt, Y+S, Y, Kt and K groups, respectively. Dry matter, crude cellulose and protein digestibility were determined to be 65.67, 62.45. 63.67, 61.23, 57.99, 59.59% (P<0.05); 67.21, 65.21. 67.05, 64.07, 62.28. 62.61% (P<0.05): and 65.85. 62.11, 63.35, 60.47, 55.02, 57.92% (P<0.05) in the Pc, Pt. Y+S. Y, Kt and Kc groups, respectively. In this study it was determined that in terms of feed quality and nutrient matter digestibility the P group was better than the other groups, and that the K group was better than the Kt group.
Körpe arpa hasilinin farkli yöntemlerle konserve edilmesinin yem kalitesi ile toklularda besin maddelerinin sindirilme derecesi üzerine etkisi
Keywords: silage; barley; food intake; digestibility; lambs